6x-3=-11

Simple and best practice solution for 6x-3=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=-11 equation:


Simplifying
6x + -3 = -11

Reorder the terms:
-3 + 6x = -11

Solving
-3 + 6x = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 6x = -11 + 3

Combine like terms: -3 + 3 = 0
0 + 6x = -11 + 3
6x = -11 + 3

Combine like terms: -11 + 3 = -8
6x = -8

Divide each side by '6'.
x = -1.333333333

Simplifying
x = -1.333333333

See similar equations:

| m=10-x | | 8.1+1.8h=-7.2 | | (M-7)(m-3)=0 | | 45-61=4x-2x | | 1.5x+0.5=12 | | 3x-4x=-22 | | bx-ay+2z=-19 | | 72y+4.7=62.3 | | 6x^2-3=x^3-169 | | 4a+5b+c=6 | | -x-3(2)=-11 | | 9r^2+2r-24=0 | | 30x=540 | | 5-4k=12x+7 | | x^2+7x+20=3x+17 | | -9y+3x=-9 | | 95m-2=80a+3 | | 6=10(k+.6) | | 2x+22+122=14x | | m/(-3)=-5-18 | | 6x-5+8x-2x-3=9w-24 | | 0.40x+0.25(140)=0.20(113) | | 5t-2=3t-8+8t | | 3x(5)+3=18 | | m^2+7m+5=0 | | 10t-4t=-11 | | 2x+19=8x-41 | | 12p+3q-5p+8q= | | 3a-b+c=10 | | 16x+8=32x+16 | | 1.055=x^15 | | x^2+7x=-2x+10 |

Equations solver categories